Music school and innovations: attitude of instrument subject teachers - Gabnytė, Giedrė; Strakšienė, Diana (Social Welfare: Interdisciplinary Approach, 2017)
The article deals with the attitude of music school teachers (N=367) towards music innovations and their dissemination. This analysis grounds on a significant research of attitudes of music pedagogues working in schools in Lithuania; this research aims at diagnosing how current music education changes/remains unchanged in the context of paradigm change, under the impact of manifestation of professional attitudes of pedagogues. Obtained results of the empirical research provided valuable information on delivered music education and possible innovations in its various fields. Therefore, the present article will present a relevant part of the mentioned research – pedagogues’ attitudes towards innovations selected and suggested by researchers, hypothetically postulating that they are the most lacking in current music education. The research found out that pedagogues were quite favourable towards dissemination of innovations. Education of people with disabilities and training of adults were supported the most, whereas the least approval was expressed towards the change of the assessment system and possibilities for organisation of group learning. Pedagogues treat new disciplines, such as improvisation, ensemble, accompaniment, reading notes, performing music aurally, as important.
Keywords: music school; music education; attitude of teachers; innovation; innovations in music education